AVALIAÇÃO DA COMPOSIÇÃO QUÍMICA E APLICAÇÃO BIOLÓGICA DO ÓLEO ESSENCIAL DA Lantana aff. Lilacina Desf. (MILHO DE GRILO),UMA Verbenaceae - MACIEL, Luênery Henrique de Oliveira; ADÃO, Cintia Cristina Domiciano; SCHOT, Joice de Oliveira; SILVA, Rogério César de Lara (ANAIS DO ENIC, 2022)
-